Sistem Monitoring Kebugaran Kardiorespirasi dengan Pulse Sensor dan Load Sensor Menggunakan Non-Excercise Prediction Method - Rifqi Anshari; Rizal Maulana; Dahnial Syauqy (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Cardiorespiratory fitness connected with the ability function of heart, blood vessel, lungs and muscle to supply oxygen when do physical activity. There is a proof that own good cardiorespiratory fitness can reduce cardiovascular disease like heart attack and stroke. Therefore it's important to have good cardiorespiratory fitness. Cardiorespiratory fitness can be measured by level maximum oxygen body can take (VO2max). There is a method for prediction of VO2max without doing physical activity using heart rate rest, body weight and age (non-excercise prediction method). Measuring Heart rate and body weight for calculation VO2max with non-excercise prediction method use 2 sensors, pulse sensor and load sensor. In order to facilitate VO2max calculation and displaying attractive result, then used android OS-based devices as an intermediary by utilizing the HC-05 Bluetooth module as a medium of data exchange. Applications built on android OS based devices are also equipped with suggestions for improving good VO2max so that it can be a guide for users. Tests on sensors in VO2max measurements resulted in an error of 8.12% for pulse sensors and 0.92% error results for load sensor. The maximum effective range that can be done by the Bluetooth module HC-05 is 10 meters. The method performed can easily measure VO2max without having to do physical activity so as to facilitate in the supervision of cardiorespiratory fitness of the body.